Pemanfaatan Pesawat Terbang Tanpa Awak untuk Pengamanan Perbatasan Kalimantan dan Dampaknya Terhadap Ketahanan Wilayah - Syaiful Anwar (Jurnal Ketahanan Nasional, 2021)
The Indonesian Government has carried out security in the Indonesia-Malaysia border area by placing various cross-border posts and security posts. The use of Unmanned Aerial Vahicles (UAVs) has proven to be very helpful in reconnaissance, and data collection, even in very difficult terrain conditions. This study aimed to find out more about the benefits of using UAVs in securing land borders in Kalimantan and their impact on the regional resilience.This study was a qualitative research, using a case study approach, which was used because the Researcher wanted to examine in depth the use of the UAV in a limited context and time period. The data used was primary data obtained from relevant informants, and secondary data obtained from official government documents and obtained by the previous researchers. To get the findings, the Researcher analyzed them using the theory of border area management and the theory of national resilience.The findings from the analysis was in the form of the impact of the use of UAVs, that the utilization has been increasing the resilience of border areas by realizing more effective and efficient border management. Thus, within the border area there has been an increase in the protection of various aspects of the regional resilience.